2004
DOI: 10.1200/jco.2004.01.159
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Survey of Fertility Issues in Young Women With Breast Cancer

Abstract: Fertility after treatment is a major concern for young women with breast cancer. There is a need to communicate with and educate young patients regarding fertility issues at diagnosis and a need for future research directed at preserving fertility for young breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
489
4
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(553 citation statements)
references
References 45 publications
45
489
4
15
Order By: Relevance
“…Early detection and improvements in screening have increased the number of premenopausal women diagnosed with breast cancer, while advances in treatment options have contributed to declining breast cancer mortality rates [1,2]. With increasing numbers of breast cancer survivors, quality of life issues such as the delayed effects of cancer treatments and fertility preservation have gained prominence [3][4][5][6]. Embryo and mature oocyte cryopreservation are currently the most established techniques for fertility preservation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and improvements in screening have increased the number of premenopausal women diagnosed with breast cancer, while advances in treatment options have contributed to declining breast cancer mortality rates [1,2]. With increasing numbers of breast cancer survivors, quality of life issues such as the delayed effects of cancer treatments and fertility preservation have gained prominence [3][4][5][6]. Embryo and mature oocyte cryopreservation are currently the most established techniques for fertility preservation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used adjuvant chemotherapy regimens use agents with a well-recognized negative impact on fertility [4,13]. Studies have shown that reproductive concerns play an important role for young women diagnosed with breast cancer [14,15]. In a study using a Web-based survey, 29% of women stated that infertility concerns influenced their treatment decisions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Infertility or concerns about (in)fertility due to cancer treatment have a negative influence on quality of life (Partridge et al, 2004;Wenzel, DeAlba, et al, 2005). Therefore, interest in possibilities for fertility preservation (FP) has increased.…”
Section: Introductionmentioning
confidence: 99%